Fluid chemistry in the Solitaire and Dodo hydrothermal fields of the Central Indian Ridge. Issue 5 (11th November 2016) - Kawagucci, S.; Miyazaki, J.; Noguchi, T.; Okamura, K.; Shibuya, T.; Watsuji, T.; Nishizawa, M.; Watanabe, H.; Okino, K.; Takahata, N.; Sano, Y.; Nakamura, K.; et al.
Abstract: Fluid chemistry and microbial community patterns in chimney habitats were investigated in two hydrothermal fields located at the Central Indian Ridge. Endmember hydrothermal fluid of the Solitaire field, located ~3 km away from the spreading center, was characterized by moderately high temperature (307°C), Cl depletion (489 mm ), mildly acidic pH (≥4.40), and low metal concentrations (Fe ≤ 105 μm and Mn = 78 μm ). Chloride depletion indicates that the subseafloor source fluid had undergone phase separation at temperatures higher than ~390°C while the metal depletion was likely attributable to fluid alteration occurring at a venting temperature of around 307°C. These different temperature conditions suggested from fluid chemistry might be associated with an off‐spreading center location of the field that allows subseafloor fluid cooling prior to seafloor discharge. The microbial community in the chimney habitat seemed comparable to previously known patterns in typical basalt‐hosted hydrothermal systems. Endmember hydrothermal fluid of the Dodo field, standing on center of the spreading axis, was characterized by high H2 concentration of 2.7 mm . The H2 enrichment was likely attributable to fresh basalt–fluid interaction, as suggested by the nondeformed sheet lava flow expansion around the vents. Thermodynamic calculation of the reducing pyrite–pyrrhotite–magnetite (PPM) redox buffer indeed reproduced the H2 enrichment. The quantitative cultivation test revealed that the microbial community associated with the hydrothermal fluid hosted abundant populations of (hyper)thermophilic hydrogenotrophic chemolithoautotrophs such as methanogens. The function of subseafloor hydrogenotrophic methanogenic populations dwelling around the H2 ‐enriched hydrothermal fluid flows was also inferred from the 13 C‐ and D‐depleted signature of CH4 in the collected fluids. It was observed that the hydrothermal activity of the Dodo field had ceased until 2013.